2008
DOI: 10.1152/ajpheart.91449.2007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and biochemical characterization of basal and starvation-induced autophagy in isolated adult rat cardiomyocytes

Abstract: Autophagy is simultaneously a mode of programmed cell death and an important physiological process for cell survival, but its pathophysiological significance in cardiac myocytes remains largely unknown. We induced autophagy in isolated adult rat ventricular cardiomyocytes (ARVCs) by incubating them in glucose-free, mannitol-supplemented medium for up to 4 days. Ultrastructurally, intracellular vacuoles containing degenerated subcellular organelles (e.g., mitochondria) were markedly apparent in the glucose-star… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
33
0
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 30 publications
4
33
0
1
Order By: Relevance
“…Uncontrolled increases in cytosolic Ca 2+ result in supercontraction of sarcomeres, which destroys the plasma membrane and cytoplasmic architecture-i.e., causes necrotic cell death. As shown in our study, 6 inhibitors of autophagy increased the incidence of cardiomyocyte necrosis accompanying ATP reduction. We therefore supposed that necrosis might be the result of energy depletion (primary necrosis) caused by suppression of the recycling needed for energy production via autophagy, though the possibility that ATP levels dropped as the result of cell rupture was not excluded.…”
Section: Difficulty In Defining Death Of Adult Cardiomyocytessupporting
confidence: 84%
See 2 more Smart Citations
“…Uncontrolled increases in cytosolic Ca 2+ result in supercontraction of sarcomeres, which destroys the plasma membrane and cytoplasmic architecture-i.e., causes necrotic cell death. As shown in our study, 6 inhibitors of autophagy increased the incidence of cardiomyocyte necrosis accompanying ATP reduction. We therefore supposed that necrosis might be the result of energy depletion (primary necrosis) caused by suppression of the recycling needed for energy production via autophagy, though the possibility that ATP levels dropped as the result of cell rupture was not excluded.…”
Section: Difficulty In Defining Death Of Adult Cardiomyocytessupporting
confidence: 84%
“…In the heart, autophagic cardiomyocytes are observed under pathological conditions such as heart failure, pressure overload and myocardial ischemia and/or reperfusion, 2-5 but their functional significance remains controversial. In our recent study, 6 we examined the functional role of starvation-induced autophagy in isolated adult cardiomyocytes, a terminally differentiated cell with a highly specialized structure and function. We found that inhibiting the autophagic process by suppressing either phagophore formation using 3-methyladenine or the digestion step using leupeptin significantly reduced survival among cardiomyocytes; conversely, enhancing autophagy using rapamycin increased survival.…”
Section: Functional Significance Of Starvation-induced Autophagy In Amentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, autophagy in cardiomyocytes is required for normal cellular function in the basal state. Inhibition of autophagy in cultured adult rat ventricular cardiomyocytes results in cell death, further supporting the essential role of autophagy in cardiomyocyte cell survival (17,18). Overall, autophagy is required for normal cellular function and for response to multiple types of stress in the neonatal and adult heart.…”
Section: Discussionmentioning
confidence: 69%
“…In the adult heart, autophagy is required for homeostasis, because cardiac specific loss of Atg5 leads to cardiac hypertrophy, left ventricular dilation, contractile dysfunction, and ultimately heart failure (16). During nutrient deprivation, autophagy is induced in the adult mouse heart in vivo and in cultured neonatal rat cardiomyocytes (13,17). Increased cardiac autophagy also occurs with dilated cardiomyopathy, heart failure, ischemia/reperfusion, aortic stenosis, and in hibernating myocardium (11, 18 -21).…”
mentioning
confidence: 99%